2007
DOI: 10.1007/s10832-007-9218-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of doped Ni2+ on the dielectric properties of NiO-BaTiO3 composites

Abstract: NiO-BaTiO 3 composites were prepared by sintering BaTiO 3 together with NiO in air at 1300°C. Microstructure and morphology of the composites were detected by XRD and SEM, and the dielectric properties were measured by LCZ meter. The results indicate that the perovskite phase is formed in fact in status of solid solution doped with Ni 2+ , although only a small amount of Ni ions can dissolve into the perovskite phase. Ni doping decreases the formation temperature of the composite without inhibiting the grain g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…41 In the bulk composites, the addition of NiO was more effective in broadening dielectric constant peaks and values. 42,43 For the BTO:NiO composties, the switching polarities for the two semiconductors are opposite to each other and the interdiffusion between the BTO grains and NiO can affect the rather complex dielectric dispersion and conductivity spectra. 44,45 Hence, the enhanced polarization and dielectric constant may be realized by controlling the geometry structures of NiO with BTO in the BTO:NiO nanocomposite thin lms.…”
Section: Introductionmentioning
confidence: 99%
“…41 In the bulk composites, the addition of NiO was more effective in broadening dielectric constant peaks and values. 42,43 For the BTO:NiO composties, the switching polarities for the two semiconductors are opposite to each other and the interdiffusion between the BTO grains and NiO can affect the rather complex dielectric dispersion and conductivity spectra. 44,45 Hence, the enhanced polarization and dielectric constant may be realized by controlling the geometry structures of NiO with BTO in the BTO:NiO nanocomposite thin lms.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the dielectric properties may be distinctly increased through the percolation effect near the percolation threshold. [8][9][10][11][12][13][14] However, the universal percolation threshold is very low (< 0.2). Even though we have prepared a percolative FFC with comparatively high percolation threshold (about 0.5) and high dielectric properties (about 10 times higher than that of the original perovskite phase) by the conventional ceramic method (CCM), [4] the percolation threshold (the content of ferrite phase) was not high enough and the permeability was only 20 % of pure magnetic ferrite.…”
mentioning
confidence: 99%
“…These requirements seems very hard to achieve by CCM. [4,[8][9][10][11][12][13][14][15][16] Therefore, it is of great importance to find a new method to produce the ferrite well surrounded by only a thin perovskite layer, which can avoid connection among the ferrite particles. If this can be achieved, on the one hand, the percolation threshold and thus the permeability of the FFCs can be increased, and, on the other hand, the permittivity can be increased significantly owing to the thinner perovskite layer.…”
mentioning
confidence: 99%
“…19 The doping of barium titanate with nickel decreased the dielectric constant and the Curie temperature and also resulted in a smearing of the ferroelectric phase transition in BaTiO 3 as the Ni concentration increased. [20][21][22] The kinetics of the transformation between the cubic and hexagonal phases in BaTiO 3 doped with various impurities was studied in Ref. 14. It was shown that nickel favors the transition to the hexagonal phase, while the doping of BaTiO 3 with strontium prevents this transition.…”
Section: Introductionmentioning
confidence: 99%